Patterns of Genetic Diversification in the Invasive Hybrid Plant Pathogen Phytophthora × alni and Its Parental Species P. uniformis - Mizeriene, Goda; Cerny, Karel; Zyka, Vladimir; Bakonyi, József; Nagy, Zoltán Árpád; Oliva, Jonas; Redondo, Miguel Angel; Corcobado, Tamara; Martín-García, Jorge; Prospero, Simone (Phytopathology, 2020)
In pathogenic fungi and oomycetes, interspecific hybridization may lead to the formation of new species having a greater impact on natural ecosystems than the parental species. From the early 1990s, a severe alder (Alnus spp.) decline due to an unknown Phytophthora species was observed in several European countries. Genetic analyses revealed that the disease was caused by the triploid hybrid P. × alni, which originated in Europe from the hybridization of P. uniformis and P. × multiformis. Here, we investigated the population structure of P. × alni (158 isolates) and P. uniformis (85 isolates) in several European countries using microsatellite markers. Our analyses confirmed the genetic structure previously observed in other European populations, with P. uniformis populations consisting of at most two multilocus genotypes (MLGs) and P. × alni populations dominated by MLG Pxa-1. The genetic structure of P. × alni populations in the Czech Republic, Hungary and Sweden seemed to reflect the physical isolation of river systems. Most rare P. × alni MLGs showed a loss of heterozygosity (LOH) at one or a few microsatellite loci compared with other MLGs. This LOH may allow a stabilization within the P. × alni genome or a rapid adaptation to stress situations. Alternatively, alleles may be lost because of random genetic drift in small, isolated populations, with no effect on fitness of P. × alni. Additional studies would be necessary to confirm these patterns of population diversification and to better understand the factors driving it.
Keywords: ekosystém; Genetic Variation; Švédsko; Ecosystem; nemoci rostlin; Genotype; Europe; Evropa; Sweden; genotyp; genetická variace; mikrosatelitní repetice; Plant Diseases; Phytophthora; Microsatellite Repeats